Persistência e liberação de macronutrientes e silício da fitomassa de crotalária em função da fragmentação - da Costa, Claudio Hideo Martins [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; Soratto, Rogério Peres [UNESP]; Ferrari Neto, Jayme [UNESP] (My University, 2012)
The persistence of straw, as well as the dynamics of nutrients release of it, are important aspects to consider in the choice of plants for composition of crop rotations in a no tillage system. Thus, the objective of this work was to evaluate the decomposition rate and macronutrients and silicon (Si) release from sunn hemp (Crotalaria juncea L.) phytomass, as a function of management, with and without fragmentation. A randomized blocks design, with four replications, in a factorial 2×6, constituted by two aboveground phytomass management after 75 days after emergence (with and without mechanical fragmentation) and six sampling times (0, 18, 32, 46, 74 and 91 days after management (DAM)), were evaluated the decomposition rate and nutrient release from sunn hemp biomass. The mechanical fragmentation of sunn hemp straw did not change the decomposition and macronutrients release. The maximum release rates occurred 0-18 DAM. Potassium is the most rapidly available nutrient, while the silicon is more slowly released to the ground. Over time there has been increasing Si content in the straw.
Persistence and release of macronutrients and silicon of sunnhemp phytomass as affected by fragmentation
Keywords: Cover crop; Crotalaria juncea L.; Decomposition rate; Nutrient cycling; Straw management